2016
DOI: 10.21873/anticanres.11124
|View full text |Cite
|
Sign up to set email alerts
|

miR-21, miR-221 and miR-150 Are Deregulated in Peripheral Blood of Patients with Colorectal Cancer

Abstract: The Aim of this study was to evaluate the expression levels of miR-21, miR-221, miR-150, let-7a and miR-126a in peripheral blood of 71 patients with colorectal cancer and 80 matched healthy control individuals. We determined expression levels of these microRNAs in peripheral blood samples and used small nucleolar RNA (RNU48) as an internal control. Expression levels of miR-21 (p<0.0001) and miR-221 (p<0.0001) were significantly higher, whereas expression levels of miR-150 (p=0.0054) were significantly lower in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Increased expression of miR-21 and miR-221 was previously found in peripheral blood samples in patients with colorectal cancer (10,13). We also found that miR-221 had higher expression in rectal than in colonic cancer and than in healthy controls.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Increased expression of miR-21 and miR-221 was previously found in peripheral blood samples in patients with colorectal cancer (10,13). We also found that miR-221 had higher expression in rectal than in colonic cancer and than in healthy controls.…”
Section: Discussionsupporting
confidence: 79%
“…We also found that miR-221 had higher expression in rectal than in colonic cancer and than in healthy controls. Moreover, expression of miR-21 and miR-221 was more pronounced at an advanced tumour stage (11)(12)(13).…”
Section: Discussionmentioning
confidence: 95%
“…us, there is a compelling need to identify molecular biomarkers for mass screening and early diagnosis of CRC. A report showed that miR-221 (p < 0.0001) was significantly higher in peripheral blood of 71 patients with colorectal cancer in comparison with 80 matched healthy control individuals [107]. Yau and colleagues evaluated the plasma miR-221 level [108] and the stool miR-221 level [109] and found that the plasma miR-221 had a high sensitivity (86%) but poor specificity (41%) and an AUC of only 0.61.…”
Section: Role Of Mir-221/222 In Colorectal Cancermentioning
confidence: 99%
“…An antecedent study has reported that microRNA-150-5p (miR-150-5p) exacerbates cellular metastasis in non-small cell lung cancer (Li et al 2016). Its role in the progression of colorectal cancer has also been explored (Aherne et al 2015;Sarlinova et al 2016). Deserved to be mentioned, miR-150-5p is sponged by circular RNA ZNF609 (a competitive endogenous RNA) to mediate AKT3 expression in Hirschsprung's disease (Peng et al 2017).…”
Section: Introductionmentioning
confidence: 99%